The Effect of Store Atmosphere on Impulse Buying During the Covid-19 Pandemic (Study on Consumers of Transmart Carrefour Medan Fair) - Ferdygustav Fiansyah Tarigan (Journal Boas : Business, Economics, Accounting And Management, 2022)
Impulsive buying this can interfere with the thoughts and attitudes of a consumer, when purchases are made on the basis of needs and daily routines, of course, consumers will not spend money on goods that they do not need. Meanwhile, impulsive buying tends to prioritize momentary emotions regardless of whether the product purchased is a need that must be met. A comfortable store atmosphere is one of the things that influences a consumer when they want to choose the product they want to buy. This study aims to determine and analyze the effect of Store atmosphere on Impulse Buying (Study on Consumers of Transmart Carrefour Plaza Medan Fair). This study uses the associative method with a quantitative approach. The population in this study were consumers of Transmart Carrefour Medan Fair and the sample in this study amounted to 96 people. The data analysis method used is validity and reliability test, classical assumption test, simple regression analysis test, hypothesis test (t-test) and coefficient of determination test. The test was carried out using the help of SPSS 22.0. Based on the research, it was found that the store atmosphere variable had a positive and significant effect on impulse buying during the Covid-19 pandemic. Where the t-count results for the store atmosphere variable are 4,842 and the t-table value is 1,661, it is concluded that t-count > t-table (4,842 > 1,661) with a significance value of 0.000 < 0.05. The r-square value is 0.200, where the correlation coefficient value shows that the relationship between store atmosphere variables has a positive and significant influence on impulse buying is weak. classical assumption test, simple regression analysis test, hypothesis test (t-test) and coefficient of determination test. The test was carried out using the help of SPSS 22.0. Based on the research, it was found that the store atmosphere variable had a positive and significant effect on impulse buying during the Covid-19 pandemic. Where the t-count results for the store atmosphere variable are 4,842 and the t-table value is 1,661, it is concluded that t-count > t-table (4,842 > 1,661) with a significance value of 0.000 < 0.05. The r-square value is 0.200, where the correlation coefficient value shows that the relationship between store atmosphere variables has a positive and significant influence on impulse buying is weak. classical assumption test, simple regression analysis test, hypothesis test (t-test) and coefficient of determination test. The test was carried out using the help of SPSS 22.0. Based on the research, it was found that the store atmosphere variable had a positive and significant effect on impulse buying during the Covid-19 pandemic. Where the t-count results for the store atmosphere variable are 4,842 and the t-table value is 1,661, it is concluded that t-count > t-table (4,842 > 1,661) with a significance value of 0.000 < 0.05. The r-square value is 0.200, where the correlation coefficient value shows that the relationship between store atmosphere variables has a positive and significant influence on impulse buying is weak. hypothesis test (t-test) and coefficient of determination test. The test was carried out using the help of SPSS 22.0. Based on the research, it was found that the store atmosphere variable had a positive and significant effect on impulse buying during the Covid-19 pandemic. Where the t-count results for the store atmosphere variable are 4,842 and the t-table value is 1,661, it is concluded that t-count > t-table (4,842 > 1,661) with a significance value of 0.000 < 0.05. The r-square value is 0.200, where the correlation coefficient value shows that the relationship between store atmosphere variables has a positive and significant influence on impulse buying is weak. hypothesis test (t-test) and coefficient of determination test. The test was carried out using the help of SPSS 22.0. Based on the research, it was found that the store atmosphere variable had a positive and significant effect on impulse buying during the Covid-19 pandemic. Where the t-count results for the store atmosphere variable are 4,842 and the t-table value is 1,661, it is concluded that t-count > t-table (4,842 > 1,661) with a count > t-table (4,842 > 1,661) with a significance value of 0.000 < 0.05. The r-square value is 0.200, where the correlation coefficient value shows that the relationship between store atmosphere variables has a positive and significant influence on impulse buying is weak.